ADAPTING MODERN METHODS OF LECTURING IN NIGERIAN UNIVERSITIES: A CRITIQUE - Balogun, M; Tejumola, Abduhaadi A; Yisa, B Kareem; Balogun, Ilyas O (PEOPLE: International Journal of Social Sciences, 2018)
Different disciplines have explored the concept of lecturing from different perspectives. However, adapting some modern methods of lecturing in Nigerian universities have not been systematically studied. Therefore, this paper examines critically the modern methods of lecturing in our modern days tertiary institutions in Nigeria.In agreement with other researches, this paper notes that there are many challenges facing the methods of teaching in Nigerian Universities today. Triangulation method was used to gather information for this paper, and both primary and secondary sources were used to obtain information for this article. The findings of this paper show that the traditional lecture method will not lead to much educational achievements unless it is combined with interactive engagements with the students and prompt feedback from the tutorsThe paper recommends that if Government could live up to her expectation by provision of basic amenities and state-of-the-arts teaching facilities to the tertiary institutions, the phenomenon could be reduced. A concerted effort is therefore needed among all stake holders in the education sector for the task of promoting effective teaching in our tertiary institutions.